Exploring hybrid ventilation in cold climates: energy efficiency, thermal comfort, and future climate adaptation in a nZEB case study in Norway - Rabani, Mehrdad; Sønderland, Simen; Rabani, Mehran (Frontiers in Built Environment, 2025)
The Climate House at Tøyen in Oslo is a nearly Zero Emission Building (nZEB) designed for exhibitions and educational purposes. It operates with a hybrid ventilation system, where natural ventilation via operable windows serves as the primary strategy, supplemented by mechanical ventilation when natural ventilation alone cannot maintain acceptable indoor thermal comfort and air quality. However, monitoring and analysis indicate that the current ventilation system underperforms, particularly during the winter season, resulting in suboptimal thermal comfort and reduced energy efficiency. This study aims to investigate whether optimized hybrid ventilation control strategies can be beneficial in nZEB buildings in cold climates, both under current and future conditions. A new control strategy was tested using IDA-ICE 5.0 simulations, prioritizing mechanical ventilation while using natural ventilation as a supplement. Results show a 13% energy reduction compared to full mechanical ventilation, with improved thermal comfort and compliance with indoor air quality standards. When tested under future climate scenarios (RCP 2.6, 4.5, and 8.6), the strategy yields energy savings of 19%–21% by 2050 and up to 30% by 2100. However, under extreme heat conditions in 2100, the system may struggle with overheating, indicating the need for higher airflow rates and extended night ventilation. Overall, the findings suggest that, with adaptive control, hybrid ventilation is a promising solution for improving energy efficiency in low-energy buildings in cold climates—even as temperatures rise.